2017
DOI: 10.1021/acs.est.6b06303
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Process Combination of Photocatalytic Oxidation and Dark Reduction for the Removal of Organic Pollutants and Cr(VI) using Ag/TiO2

Abstract: We investigated a sequential photocatalysis-dark reaction, wherein organic pollutants were degraded on Ag/TiO under UV irradiation and the dark reduction of hexavalent chromium (Cr(VI)) was subsequently followed. The photocatalytic oxidation of 4-chlorophenol (4-CP), a test organic substrate, induced the generation of degradation intermediates and the storage of electrons in Ag/TiO which were then utilized for reducing Cr(VI) in the postirradiation period. The dark reduction efficiency of Cr(VI) was much highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
76
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 206 publications
(78 citation statements)
references
References 45 publications
0
76
0
2
Order By: Relevance
“…[68] This study essentially showedt hat stored electrons were capable of reducingh eavymetal ions in the dark as well. [70] It was reportedt hat the photocatalytic oxidationo f4 -CP produced intermediate compounds and stored electrons in the Ag/TiO 2 system forf urtheru tilizationt or educe Cr VI in the dark. In practice, the presence of O 2 inhibits the storageo fe lectrons by scavenging them.…”
Section: Heavy-metal Reductionsmentioning
confidence: 99%
See 1 more Smart Citation
“…[68] This study essentially showedt hat stored electrons were capable of reducingh eavymetal ions in the dark as well. [70] It was reportedt hat the photocatalytic oxidationo f4 -CP produced intermediate compounds and stored electrons in the Ag/TiO 2 system forf urtheru tilizationt or educe Cr VI in the dark. In practice, the presence of O 2 inhibits the storageo fe lectrons by scavenging them.…”
Section: Heavy-metal Reductionsmentioning
confidence: 99%
“…In as ingle reaction, organic pollutants, such as 4-CP,f ormic acid, humic acid, or ethanol,w ere degraded with Ag/TiO 2 under UV light, followed by the dark reduction of hexavalent Cr VI . [70] It was reportedt hat the photocatalytic oxidationo f4 -CP produced intermediate compounds and stored electrons in the Ag/TiO 2 system forf urtheru tilizationt or educe Cr VI in the dark. Accordingly,t he dark reduction of Cr VI was much higherf or Ag/TiO 2 (87 %) and continued for few hours.T he observed dark-reduction efficiency of the Ag/TiO 2 system was proposed to be the collective effects of 1) adsorption,2 )chemical reduction by intermediates of 4-CP degradation,a nd 3) reduction by electrons stored in Ag (Figure 13).…”
Section: Heavy-metal Reductionsmentioning
confidence: 99%
“…Recent reports have shown that highly efficient plasmonic photocatalysts such as Ag/g‐C 3 N 4 , Ag/TiO 2 , Ag/AgVO 3 , Ag/Ag 3 PO 4 , Ag/Ag 2 MoO 4 , and Ag/Ag 2 WO 4 can be prepared and their results indicate that Ag decoration can dramatically enhance the photocatalytic performance of the pure photocatalyst via the SPR effect. Recently, considerable efforts have been placed on the design and fabrication of heterojunctions to improve the applications of AgX‐based materials .…”
Section: Introductionmentioning
confidence: 99%
“…Besides metal cations, the real wastewater contains several kinds of anions and organic matter. The coexistence of high‐affinity ligands such as PO 4 3− and organic pollutants can hinder the removal efficiency of Cr(VI) and affect regeneration of the adsorbents , …”
Section: Resultsmentioning
confidence: 99%
“…The coexistence of high-affinity ligands such as PO 4 3− and organic pollutants can hinder the removal efficiency of Cr(VI) and affect regeneration of the adsorbents. 57,58…”
Section: Examination Of a Real Samplementioning
confidence: 99%